Urban planning laboratory - Cochrane, Joe (2010)
The future productive capacity of many Asian countries depends on making their cities more sustainable.
Urbanization as a driver of development -- Hundreds of billions of dollars needed -- Making deals -- Growing Asian slums -- Going beyond government.
Keywords: Sustainability -- Asia; Urbanization -- Asia